Living with Gorillas? Lessons from Batwa-Gorillas’ Convivial Relations at Bwindi Forest, Uganda - Ampumuza, Christine (Wolters Kluwer India Pvt. Ltd, 2022)
Abstract In recent years, convivial conservation has been proposed as a better alternative to fortress conservation by working with marginalised communities. This is a welcome development because most of the injustices and failures of fortress conservation arose from neglecting local communities’ view of being with nature, and knowledges of nature (plural of knowledge highlights that there are multiple ways and types of acquiring and transmitting knowledge through generations). A critical analysis of the conservation literature indicates a disharmony between the indigenous ways, and Northern ways of being with nature—an ontological discord in conservation. This article considers convivial conservation as starting point to address this discord. Based on the content analysis of stories of Batwa’s historical relations with gorillas, unstructured interviews, ethnographic village stays, and empirical observations, we argue that open-mindedness—to learn from, to be affected by and affect our fellow dwellers on earth (human and non-human)—marks the starting point of convivial living. Therefore, convivial conservation can further be enriched by expanding the scope of historical reparations to include knowledges that have been historically excluded. To do so, convivial conservation scholars need to emphasise the co-creation of knowledge with their human and non-human counterparts. By doing so, these scholars will safeguard against marginalising other ways of knowing, thus achieving its transformative agenda.
Keywords: Convivial conservation, Batwa, gorillas, indigenous ontologies, Uganda